Institutional Design Analysis In The Governance Of Slum Settlement Management In Sukabumi City - Semedi, Adilla Bintang Putri; Purwanti, Dian; Mulyadi, Andi (UIR Press, 2026)
This study analyses the institutional design in the governance of slum-settlement management in Sukabumi City, a strategic issue which, despite showing progress, continues to advance slowly in comparison with the scale of the problem. The designated slum area of 260.53 hectares in 2021 was successfully reduced to 162.78 hectares in 2024; however, the rate of reduction remains uneven and has not reflected the ideal acceleration. This study employs a qualitative method with a descriptive approach to examine how rules, actors, interaction patterns, and institutional performance influence the effectiveness of handling efforts. The findings indicate that the slow progress is not caused by a lack of programmes, but by weaknesses in institutional design that result in suboptimal coordination among local government units. The prevailing rules do not possess strong binding power due to the absence of comprehensive local regulations, whilst the dominance of the physical sector causes cross-sectoral programmes to be misaligned with needs in the field. Interactions among actors tend to strengthen only when integrated programmes are present, and weaken again once the programmes conclude, thereby undermining the sustainability of handling efforts. Supporting factors such as experience from national programmes, cross-sectoral coordination, and initiatives from urban villages and the community have not been sufficient to overcome major obstacles including limited land availability, low economic capacity of residents, weak participation, and the suboptimal role of the private sector. This study asserts that accelerating slum management depends greatly on strengthening institutional design so that cross-sectoral collaboration can operate consistently and sustainably.